2001
DOI: 10.1242/dev.128.16.3169
|View full text |Cite
|
Sign up to set email alerts
|

Functioning of theDrosophila orbgene ingurkenmRNA localization and translation

Abstract: The orb gene encodes an RNA recognition motif (RRM)-type RNA-binding protein that is a member of the cytoplasmic polyadenylation element binding protein (CPEB) family of translational regulators. Early in oogenesis, orb is required for the formation and initial differentiation of the egg chamber, while later in oogenesis it functions in the determination of the dorsoventral (DV) and anteroposterior axes of egg and embryo. In the studies reported here, we have examined the role of theorb gene in the gurken (grk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Interestingly, expression of the PLP-GFP transgene partially restored embryonic viability (53% hatched, p<0.0001, orb vs. PLP-GFP; orb by chi-squared test), supporting a genetic interaction between orb and plp required for viability (Figure 6D). Orb likely further supports embryonic viability through regulating other mRNA targets or protein partners (Chang et al, 2001;Mansfield et al, 2002;Norvell et al, 2015). Nonetheless, our data argue that plp is a critical downstream target subject to Orb regulation.…”
Section: Orb-dependent Regulation Of Plp Supports Genome Stabilitymentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, expression of the PLP-GFP transgene partially restored embryonic viability (53% hatched, p<0.0001, orb vs. PLP-GFP; orb by chi-squared test), supporting a genetic interaction between orb and plp required for viability (Figure 6D). Orb likely further supports embryonic viability through regulating other mRNA targets or protein partners (Chang et al, 2001;Mansfield et al, 2002;Norvell et al, 2015). Nonetheless, our data argue that plp is a critical downstream target subject to Orb regulation.…”
Section: Orb-dependent Regulation Of Plp Supports Genome Stabilitymentioning
confidence: 70%
“…Embryonic lethality in orb mutants is largely attributed to the requirement of Orb in establishing the embryonic patterning axes via its role in mediating localization and translation of osk and grk mRNAs (Christerson and McKearin, 1994;Chang et al, 1999;Chang et al, 2001;Castagnetti and Ephrussi, 2003). Interestingly, expression of the PLP-GFP transgene partially restored embryonic viability (53% hatched, p<0.0001, orb vs. PLP-GFP; orb by chi-squared test), supporting a genetic interaction between orb and plp required for viability (Figure 6D).…”
Section: Orb-dependent Regulation Of Plp Supports Genome Stabilitymentioning
confidence: 72%
See 1 more Smart Citation
“…Work by other labs has shown that Grk translation in the oocyte is activated by Oo18 RNA binding protein (Orb) (4345). Orb is a cytoplasmic polyadenylation element binding protein (CPEB) that is highly expressed in the oocyte where it recruits Wispy to lengthen the grk poly(A) tail to activate its translation (44).…”
Section: Resultsmentioning
confidence: 99%
“…In the most extreme cases we observed diffuse Kin-LacZ localization in the center of the oocyte (Fig S7C white arrow and Fig S7D yellow arrow). These data indicate that the defects in osk posterior localization may be caused by loss of grk function rather than defects in the direct regulation of osk itself.Tdrd5l represses Orb protein expression in nurse cellsWork by other labs has shown that Grk translation in the oocyte is activated by Oo18RNA binding protein (Orb)(43)(44)(45). Orb is a cytoplasmic polyadenylation element binding protein (CPEB) that is highly expressed in the oocyte where it recruits Wispy to lengthen the grk poly(A) tail to activate its translation(44).…”
mentioning
confidence: 99%